2021
DOI: 10.47747/ijbme.v2i4.385
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Good Government Governance on the Financial Reports Quality: The Case of Provincial Capital Governments in Indonesia

Abstract: This study aimed to determine the relationship and effect of the GGG variable on the quality of the financial reports in municipal governments in Indonesia by implementing the IIAG (The Ibrahim Index of African Governance) indicator. The variables of this study consist of the participant, legal culture, transparency, responsiveness, public interest orientation, fairness, effectiveness and efficiency, accountability, strategic vision, and human development as independent variables and the quality of financial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The results of this study are in line with previous research who concluded that data reconciliation has a significant positive effect on the quality of financial reports (Cahyani, 2023;Choi et al, 2013;Pizzini et al, 2015;Wahyuni et al, 2018). Reconciliation competence has a positive and significant effect on the quality of the Nias Regency Regional Government's financial reports while previous research results show that internal and external reconciliations have a positive and significant effect on the quality of financial reports at BPS (Chairunnisa & Pamungkas, 2020;Masnila et al, 2021).…”
Section: Effect Of Data Reconcilliation On the Quality Of Financial R...supporting
confidence: 91%
“…The results of this study are in line with previous research who concluded that data reconciliation has a significant positive effect on the quality of financial reports (Cahyani, 2023;Choi et al, 2013;Pizzini et al, 2015;Wahyuni et al, 2018). Reconciliation competence has a positive and significant effect on the quality of the Nias Regency Regional Government's financial reports while previous research results show that internal and external reconciliations have a positive and significant effect on the quality of financial reports at BPS (Chairunnisa & Pamungkas, 2020;Masnila et al, 2021).…”
Section: Effect Of Data Reconcilliation On the Quality Of Financial R...supporting
confidence: 91%
“…However, the escalating demands for accountability have posed challenges for principals, or the community, in carrying out their own management functions effectively. Consequently, due to these limitations, the community tends to entrust the management of their resources to what they perceive as a more capable entity-the government or steward (Masnila et al, 2021). This situation emphasizes the critical need for village policies to align with the practical realities on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Taslim and Pratama's study state that regional financial performance is not able to mediate the relationship between fiscal pressure and human development index [20]. Research from Nelly Masnila, et., al also yields human development that can affect financial statements [21].…”
Section: Literature Studymentioning
confidence: 99%